Lattice-parameter change induced by accommodation of precipitate/matrix misfit; misfitting nitrides in ferrite. (1st October 2015) - Akhlaghi, M.; Steiner, T.; Meka, S.R.; Leineweber, A.; Mittemeijer, E.J.
Graphical abstract: Abstract: Upon nitriding of iron-based alloys, development of misfitting coherent nitride precipitates in a ferrite matrix induces an overall expansion of the ferrite lattice. This lattice expansion was quantitatively determined by X-ray diffraction from the change of the lattice parameter of ferrite of homogenously nitrided FeCr and FeV alloys. Adopting the experimentally verified (by X-ray diffraction and transmission electron microscopy) notion that the misfitting precipitates diffract coherently with the matrix, the extent of this hydrostatic lattice-strain component could be calculated, in general, as function of the precipitate/matrix misfit, the volume fraction of precipitates and the elastic properties of the matrix and precipitates. The experimentally observed and the predicted dependencies of lattice dilatation agree very well for both nitrided FeCr and FeV alloys. This is the first time that this type of lattice expansion was experimentally identified and quantitatively explained.